2020
DOI: 10.7717/peerj.8422
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis of potential pathway biomarkers using abnormal proteins in clubfoot

Abstract: Background As one of the most common major congenital distal skeletal abnormalities, congenital talipes equinovarus (clubfoot) affects approximately one in one thousandth newborns. Although several etiologies of clubfoot have been proposed and several genes have been identified as susceptible genes, previous studies did not further explore signaling pathways and potential upstream and downstream regulatory networks. Therefore, the aim of the present investigation is to explore abnormal pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…However, these studies do not further explore the interactions among these genes, signaling pathways, and the gene upstream and downstream regulatory networks. Recently, we found that the results of bioinformatics analyses using abnormal proteins provided experimental evidence for previously proposed hypotheses, e.g., the abnormalities of ECM, genetic, muscle, neurological, skeletal, and vascular [ 16 ]. Additionally, cellular or immune responses to external stimulus, molecular transport and metabolism were suggested as new promising etiological mechanisms in clubfoot [ 16 ].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, these studies do not further explore the interactions among these genes, signaling pathways, and the gene upstream and downstream regulatory networks. Recently, we found that the results of bioinformatics analyses using abnormal proteins provided experimental evidence for previously proposed hypotheses, e.g., the abnormalities of ECM, genetic, muscle, neurological, skeletal, and vascular [ 16 ]. Additionally, cellular or immune responses to external stimulus, molecular transport and metabolism were suggested as new promising etiological mechanisms in clubfoot [ 16 ].…”
Section: Introductionmentioning
confidence: 88%
“…Recently, we found that the results of bioinformatics analyses using abnormal proteins provided experimental evidence for previously proposed hypotheses, e.g., the abnormalities of ECM, genetic, muscle, neurological, skeletal, and vascular [ 16 ]. Additionally, cellular or immune responses to external stimulus, molecular transport and metabolism were suggested as new promising etiological mechanisms in clubfoot [ 16 ]. However, the enriched results of bioinformatics analysis with abnormal genes in clubfoot were not explored.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations